TRANSAKSI VALUTA ASING (AL-SHARF) DALAM PERSPEKTIF ISLAM - Sulhan, Muhammad (Fakultas Ekonomi, UIN Maliki Malang, 2008)
The written text attempts to explain transactional problem (trade) foreign exchange of Islamic law trade. It is caused by the international trade phenomena that won’t be free from state currency one another as a payment tool in which accelerate the traffic of international trade activity. The necessity of currency conversion in the international trade will bring up out of foreign exchange demand and supply in the foreign exchange market; it will cause foreign exchange trade transaction at last. Based on the variety of Islamic laws analysis, it is known that the foreign currency trade practice (al-sharf) is allowed if done based on each other agreement and cash, not to have a speculation (undertake something hoping for the best), there is transactional needed or aware of (saving), and if the transaction done toward the same type of currency so, it must have the same value and if it’s different, it must be done using prevailed rate of exchange (kurs) in the moment of transaction. The following types of foreign exchange transaction in the foreign exchange market, it is only spot transactional type allowed, meanwhile forward, swap, and option are forbidden because they aren’t cash and contain of maisir (speculation). Besides, the participants should pay more attention toward constrains of foreign exchange trade transaction and they should be able to avoid divergences that are forbidden in Islamic of syariah trade like extortionate, forcing and many others. In this case, these cause the transaction of foreign exchange trade is prohibited.